Asesoría a la gestión comercial de las empresas afiliadas a la cámara de comercio de Ibarra. - Perugachi, Lizandro M (2018)
The University of Otavalo through an agreement with the Chamber of Commerce of Ibarra, seeks to develop projects that strengthen this entity and therefore the commercial sector. The activities that have been carried out in the Chamber were the gathering of information on the merchants of the City, and their analysis by economic sectors of the Canton, which has Determined needs such as training in customer service, marketing, administration, continuing education among others.